The effect of STEM approach e-module -topic of free-range chicken eggs productivity on student learning outcomes in entrepreneurship courses in the era of the industrial revolution 4.0 - K Anom W; Made Sukaryawan; Eka Ad’hiya (Jurnal Pendidikan Kimia (JPKim), 2021)
The use of technology in the form of e-modules in entrepreneurship courses in the chemistry education study program, Universitas Sriwijaya is a challenge for learning in the industrial revolution era 4.0. So this study aims to determine the effect of STEM approach e-module- topic of the productivity of free-range chicken eggs on student learning outcomes in entrepreneurship courses in the era of the industrial revolution 4.0. Respondents of this study were students in the third semester of the chemical education study program at the Sriwijaya University. This research method is a quasi-experimental method, where a limited field test is carried out on previously developed e-modules. Data on student learning outcomes were obtained from the pre-test and post-test scores which were analyzed by N-Gain. The results showed that the N-Gain value was 0.937 which was classified as high category, which means that there was a significant difference in student learning outcomes before and after using the STEM e-module approach. Beside that, respondents have reported examples of creativity in business plan as a result of using STEM approach e-module- topic of free-range chicken egg productivity for the Entrepreneurship Course in Chemistry Education.  Thus, it can be concluded that there is an effect of using STEM approach module-topic of free-range chicken eggs productivity on student learning outcomes in entrepreneurship courses in the chemistry education study program, Universitas Sriwijaya. Keywords: e-module learning chemistry, industrial revolution 4.0, free-range chicken eggs